Surgical Treatment of Atrial Septal Defects - Grieshaber, Philippe; Jaschinski, Christoph; Farag, Mina; Fonseca Escalante, Elizabeth; Gorenflo, Matthias; Karck, Matthias; Loukanov, Tsvetomir (Reviews in cardiovascular medicine, 2024)
Atrial septal defects (ASDs) are among the most prevalent congenital cardiac malformations. Closure of the defect and repair of associated cardiac malformations are typically indicated if an ASD is hemodynamically significant or symptomatic. This narrative review aims to summarize key aspects of surgical ASD closures. A non-systematic literature review was conducted to cover surgically relevant aspects of (developmental) anatomy, morphology, and treatment. ASDs result from diverse developmental alterations, leading to subtype-specific associated cardiac malformations, meaning surgical therapy varies accordingly. Presently, surgical repair yields excellent outcomes for all ASD subtypes, with minimally invasive approaches, especially in adults, increasingly employed for ASD closure. Surgical ASD repair is safe with excellent results. However, familiarity with ASD subtypes and typically associated lesions is crucial for optimal patient management.